How important is human capital for growth in reforming economies? - Škare, Marinko (Technological and Economic Development of Economy, 2011)
The aim of the paper is to broaden the research on human capital providing new evidence that human capital matters for economic growth in reforming economies. We propose a new model for measuring human capital. An advantage of the proposed model consists in international comparability; money metric scale and more importantly provide solid evidence on human capital significance for economic growth. This new approach in measuring human capital proved robust to the spurious regression problem involving human capital. Study results shows that human capital is important for growth and that large educational investments are essential to boost accumulation.Article in English.Žmogiškojo kapitalo svarba pereinamosios ekonomikos augimuiSantrauka. Šio straipsnio tikslas – išplėsti mokslinius tyrimus apie žmogiškąjį kapitalą ir pateikti įrodymų, kad jis yra svarbus reformuojamos ekonomikos augimui. Siūloma nauja žmogiškojo kapitalo vertinimo metodologija, kurios pranašumai – tarptautinis lyginamumas, monetarinis vertinimas ir žmogiškojo kapitalo reikšmės ekonomikos augimui akcentavimas. Naujoji metodologija įrodė savo patikimumą vertinant žmogiškojo kapitalo kintamuosius. Empiriniai rezultatai rodo, kad žmogiškasis kapitalas yra svarbus augimui, ir tam reikia didelių investicijų švietimo srityje.Reikšminiai žodžiai: ekonomikos augimas, žmogiškasis kapitalas, švietimas, endogeninis augimas.First published online 18 Jan 2012